2008
DOI: 10.1172/jci35342
|View full text |Cite
|
Sign up to set email alerts
|

Using transcriptional profiling to develop a diagnostic test of operational tolerance in liver transplant recipients

Abstract: A fraction of liver transplant recipients are able to discontinue all immunosuppressive therapies without rejecting their grafts and are said to be operationally tolerant to the transplant. However, accurate identification of these recipients remains a challenge. To design a clinically applicable molecular test of operational tolerance in liver transplantation, we studied transcriptional patterns in the peripheral blood of 80 liver transplant recipients and 16 nontransplanted healthy individuals by employing o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
254
4
7

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 187 publications
(278 citation statements)
references
References 36 publications
13
254
4
7
Order By: Relevance
“…Of the 94 targets tested by qPCR in the same set of PBMC samples, 11 were significantly different between operationally tolerant and non-tolerant recipients (Supplemental Table 13). Eight of these 11 genes (NCR1, KLRF1, IL2RB, GZMB, SH2D1B, CLIC3, KLRC4, NCAM1), all of them preferentially expressed by NK cells, had been previously described by our group as associated with liver operational tolerance (19). In order to compare the predictive performance of liver tissue and PBMC-derived gene expression signatures in the 45 recipients from whom baseline PBMC and liver tissue qPCR expression data were available, we computed receiver operating characteristic (ROC) curves for the following three predictive signatures: (a) CDHR2, MIF, PEBP1, SOCS1, and TFRC (representative liver tissuebased signature described in Table 4); (b) SLAMF7, KLRF1, CLIC3, PSMD14, ALG8, CX3CR1, and RGS3 (representative PBMC-based signature described in ref.…”
Section: Before the Initiation Of Drug Minimization Liver Grafts Fromentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 94 targets tested by qPCR in the same set of PBMC samples, 11 were significantly different between operationally tolerant and non-tolerant recipients (Supplemental Table 13). Eight of these 11 genes (NCR1, KLRF1, IL2RB, GZMB, SH2D1B, CLIC3, KLRC4, NCAM1), all of them preferentially expressed by NK cells, had been previously described by our group as associated with liver operational tolerance (19). In order to compare the predictive performance of liver tissue and PBMC-derived gene expression signatures in the 45 recipients from whom baseline PBMC and liver tissue qPCR expression data were available, we computed receiver operating characteristic (ROC) curves for the following three predictive signatures: (a) CDHR2, MIF, PEBP1, SOCS1, and TFRC (representative liver tissuebased signature described in Table 4); (b) SLAMF7, KLRF1, CLIC3, PSMD14, ALG8, CX3CR1, and RGS3 (representative PBMC-based signature described in ref.…”
Section: Before the Initiation Of Drug Minimization Liver Grafts Fromentioning
confidence: 99%
“…Our group previously reported the results of a retrospective cross-sectional study in which we observed that drug-free operationally tolerant liver recipients and liver recipients requiring maintenance immunosuppression differed in PBMC expression patterns (19). In order to investigate the similarities between PBMC and liver tissue expression patterns, we extracted RNA samples from PBMCs collected before the initiation of drug minimization from 20 operationally tolerant and 25 nontolerant recipients (all of them from Hospital Clinic Barcelona) and performed gene expression experiments using both Affymetrix microarrays and qPCR (Supplemental Table 10).…”
Section: Before the Initiation Of Drug Minimization Liver Grafts Fromentioning
confidence: 99%
“…The study of individuals in OT may help to both understand the mechanisms involved in human allograft tolerance and determine biomarkers to discriminate this state among transplanted individuals. Indeed, some research groups, including ours, have been evaluating a variety of immunologic parameters in OT, mostly related to T-cell activity (13)(14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…This implication of gd T cells in graft rejection seemingly contrasts with the previously reported Vd1 T-cell expansion in the peripheral blood and grafts of operationally tolerant liver transplant recipients. [57][58][59] However, Sánchez-Fueyo et al recently revised their interpretation of Vd1 expansions, confirming that they relate to CMV infection and are not restricted to tolerant liver recipients. 24 Even though the Banff diagnostic criteria of antibodymediated rejection requires positive C4d peritubular capillary staining, it is now well accepted that C4d does not explain all antibody-mediated lesions.…”
Section: Discussionmentioning
confidence: 97%